Ketorolac Is Safe and Associated With Lower Rate of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis in Children With Pancreatic Duct Manipulation. Issue 4 (October 2021) - Mark, Jacob A.; Kramer, Robert E.
ABSTRACT: Objectives: Use of non-steroidal anti-inflammatory drugs (NSAIDs) for post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) prevention in pediatrics is not well studied. Because of difficulty in accurately dosing indomethacin suppositories in pediatric patients, our center has used intravenous ketorolac for PEP prevention and present data on its safety and associated PEP rates. Methods: Prospective monitoring of PEP for all patients who underwent ERCP at a pediatric tertiary care center from July 2010 to June 2018. Retrospective review of patient and procedural factors and severity of PEP. Routine use of ketorolac for PEP prevention began in 2014. Results: Two hundred and ninety-eight ERCPs were analyzed. One hundred and sixty-six patients received intraprocedural ketorolac and 132 did not. One patient had post-ERCP bleeding and bleeding rates were not significantly different between ketorolac and non-ketorolac groups (0.6% vs 0%, P = 1). Overall rates of PEP were not significantly different between the ketorolac and no ketorolac group (9% vs 13%, P = 0.29); however, for high-risk pediatric patients with injection of contrast into and/or cannulation of the pancreatic duct, the rates of PEP were significantly lower for patients who received ketorolac (11% vs 25%, P = 0.035). Conclusions: Pediatric patients undergoing ERCP with manipulation of the pancreatic duct are high risk for PEP, and ketorolac was associated with a lower rate of PEP in these patients. Ketorolac was well tolerated without a higher rate of bleeding after ERCP. These results are the first to provide evidence showing an association with intraprocedural NSAID use and lower rates of PEP in select pediatric patients. Abstract : Supplemental Digital Content is available in the text